Pengaruh Keselamatan Kerja dan Disiplin Kerja Teradap Kinerja Karyawan CV Inti Kreasi Alami Jakarta - Aldi Adrian Maulana (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
Human Resources is a very important one. Apart from affecting safety, it can also affect work discipline on employee performance. This research uses quantitative research methods, and the sample used was 35 people with a saturated sampling technique. The influence of work safety on employee performance is 0.161 > 0.05 and the calculated t value is -1.433 < 1.69389. It can be concluded that the work safety variable partially has no influence on the employee performance variable. The Influence of Work Discipline on Employee Performance. Based on the results of data processing that has been obtained, it is known that the sign value is 0.000 < 0.05 and the calculated t value is 4.557 > 1.69389. It can be concluded that the Work Discipline variable partially has a significant influence on the Employee Performance variable. The Influence of Work Safety and Work Discipline on Employee Performance. Based on the results of data processing obtained by X1 and so it can be concluded that there is a significant influence between work discipline on employee performance at CV. Jakarta Natural Creation Core.